2018
DOI: 10.1101/355057
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Signals of polygenic adaptation on height have been overestimated due to uncorrected population structure in genome-wide association studies

Abstract: All of these studies have been based on SNP associations, in most cases with 81 effect sizes discovered by the GIANT Consortium, which most recently combined 79 82 individual GWAS through meta--analysis, encompassing a total of 253,288 83 individuals. [13,14] Here, we show that the selection effects described in these 84 studies are severely attenuated and in some cases no longer significant when using 85 summary statistics derived from the UK Biobank, an independent and larger single 86 study that includes 3… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 33 publications
3
35
1
Order By: Relevance
“…However, one of our strongest signals (height) did not replicate the UK Biobank, while two other signals of selection suggested by earlier height studies also did not replicate in the UK Biobank (Turchin et al 2012;Yang et al 2015). The nonreplication of height is in concordance with other recent studies finding reduced evidence for selection on height in the UK Biobank cohort applying different methods Sohail et al 2018). The most conservative interpretation of the nonreplication of height is to suppose that some of the signals we and others observed in the GIANT cohort are driven by population stratification, and the UK Biobank analysis correctly removes this spurious contamination.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, one of our strongest signals (height) did not replicate the UK Biobank, while two other signals of selection suggested by earlier height studies also did not replicate in the UK Biobank (Turchin et al 2012;Yang et al 2015). The nonreplication of height is in concordance with other recent studies finding reduced evidence for selection on height in the UK Biobank cohort applying different methods Sohail et al 2018). The most conservative interpretation of the nonreplication of height is to suppose that some of the signals we and others observed in the GIANT cohort are driven by population stratification, and the UK Biobank analysis correctly removes this spurious contamination.…”
Section: Discussionsupporting
confidence: 83%
“…; Sohail et al. ). The most conservative interpretation of the nonreplication of height is to suppose that some of the signals we and others observed in the GIANT cohort are driven by population stratification, and the UK Biobank analysis correctly removes this spurious contamination.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, it has been reported that PS differences between populations are prone to technical and confounding biases arising especially from population genetic differences (i.e. genetic divergence) or relatedness structure between the GWAS discovery and the target data Reisberg et al 2017;Berg et al 2018;Curtis 2018;Sohail et al 2018). To assess whether some of the results in Figure 2 and Table 1 might be affected by these problems, we next concentrate on evaluating our PS in several ways.…”
Section: Polygenic Scores Show Geographic Differences In Finlandmentioning
confidence: 99%
“…, evidence for selection remains controversial40,[47][48][49][50][51]59,60,62 . It was recently reported that recent selection on increased height in Europeans has been overestimated and that estimates have been confounded by subtle population stratification40,50,51 . Our test finds an enrichment of selection evidence for both effect directions for height, across most populations except East Asians, using the large collection of UK Biobank associations.…”
mentioning
confidence: 99%